Status of urban ecology in Africa: a systematic review - Awoyemi, A.G.; Ibanez-Alamo, J.D. (Elsevier, 2023)
Urbanization is an extreme human activity and is expanding worldwide, consequently increasing the attention of scientists across research areas of urban ecology. Recent studies have warned of the lack of information from certain regions, particularly Africa, which is rapidly urbanizing. Thus, we did a detailed literature search to determine the state of knowledge in African urban ecology in the last century. We found 795 relevant papers from where data were collected and tested to understand geographic and ecological mismatches in research effort, allowing us to identify important knowledge gaps (e.g., taxonomy and scientific fields). We also tested the effect of current and future urbanization intensity, human population density, size and conservation status of ecoregions and Gross Domestic Product (GDP) on research effort. Our results suggest a low turnout of papers and a dearth of knowledge about African urban ecology. Studies were conducted in 72% of African countries, with South Africa alone accounting for almost 40% of all published papers. The studies were either conducted at the city (55%) or local/country (34%) level, suggesting the lack of transnational research collaboration. Interestingly, only country GDP and the size and conservation status of ecoregions significantly predicted the number of publications, suggesting that research effort is driven by economic reasons and the relevance of conservation in African urban ecology. We need to account for these biases to advance our understanding of the impacts of urbanization on African biodiversity.